ANALYSIS ON FAILURE OF T23 WELDED JOINS IN WATER WALL - LIU Shuai; CHEN JianJun; YAN ZhenRong; WU WenChao; YUAN WeiJie; YANG Cheng (Jixie qiangdu)
The pipeline leakage in T23 water wall of ultra-supercritical tower boiler was found after the units had been put into operation for a period of time, which seriously affected the safety of the boiler units. Fracture analysis found that the circumferential crack that caused by the axial tensile stress is the main factor for the weldment leakage.Welding process of T23 water wall tube was simulated by finite element analysis software ABAQUS, and the welding residual stress distribution field was obtained. On this basis, the influence of the assembly stress on the stress field of the welded joints of the T23 water wall tube was studied. The results show stress on the welded joints is seriously affected by the assembly stress, which could cause the leakage of the T23 water wall welded joints. The maximum bending moment can be given according to the allowable stress, which provides a reference for the construction of T23 water wall welding. The thermal fatigue caused by the temperature fluctuation of the water wall is the key factor of the annular crack propagation.